The early impact of COVID-19 on the intellectual and developmental disabilities community in California - Giselle Salinas; Yasamin Bolourian; Beth Burt; Marcia Eichelberger; Jan Blacher (Frontiers in Education, 2023)
IntroductionDuring the early beginnings of COVID-19, service providers were forced to close their doors and move their services online, causing significant disruptions for many families and communities, such as those with intellectual and developmental disabilities (IDD). In this study, we examined the extent to which COVID-19 disrupted services for the IDD community in California.MethodsSecondary data were analyzed from a survey (N = 1,082) disseminated by the Autism Society of California in May 2020. Respondents were placed into two categories: autism spectrum disorder (ASD) only (n = 794) and IDD other than ASD (n = 288).ResultsThere were significant differences in services between diagnostic groups (<.05). There was a threefold difference in loss of respite services in the ASD (4.3%) versus the IDD group (12.9%). In the ASD group, 48.5% reported no change at all in respite services received, whereas in the IDD group, 71.5% reported no change. Before the pandemic, a higher mean number of medical and therapeutic services was reported as received in the ASD group (M = 1.38) than in the IDD group (M = 1.04). However, at the time of the survey, the IDD group reported a higher mean number of such services (M = 1.32) than the ASD group (M = 1.02). Differences were also seen by race/ethnicity. Before lockdown, there were no significant differences in the mean number of services reported by race/ethnicity among the full sample. However, at the time of the survey, a significantly higher mean number of services was reported by respondents who identified as White (M = 1.26) compared to people of color (M = .91), p < .05.DiscussionTo our knowledge, this study is the first to compare services received by IDD diagnostic groups during COVID-19. Findings help elucidate the negative impact of COVID-19 on the IDD community in California, as well as inform strategies for the ongoing and post-pandemic periods.